Pulsed-periodic electron-beam treatment of quenched steel; Steel in Translation; Vol. 37, № 8 - Kolubaeva Yu. A.; Ivanov Yu. F. Yuriy Fedorovich; Devyatkov V. N.; Koval N. N. Nikolay Nikolaevich (2007, 2007)
Title screen